Impact of battery degradation on energy arbitrage revenue of grid-level energy storage. (April 2017) - Wankmüller, Florian; Thimmapuram, Prakash R.; Gallagher, Kevin G.; Botterud, Audun
Highlights: We investigate the representation of battery degradation in grid-level energy storage. We implement two different models of battery degradation within an energy arbitrage model. Battery degradation has a strong impact on lifetime profitability from energy arbitrage. Extending the battery lifetime through reduced cycling improves profitability. Abstract: This study investigates the representation of battery degradation in grid level energy storage applications. In particular, we focus on energy arbitrage, as this is a potential future large-scale application of energy storage and there is limited existing research combining the modelling of battery degradation and energy storage arbitrage. We implement two different representations of battery degradation within an energy arbitrage model, and show that degradation has a strong impact on battery energy storage system (BESS) profitability. In a case study using historical electricity market prices from the MISO electricity market in the United States, we find that the achievable net present value (at an interest rate of 10%) for a battery system with a C-rate of 1C dropped from 358 /kWh in the case considering no degradation to 194–314 /kWh depending on the battery degradation model and assumptions for end of life (EOL) criteria. This corresponds to a reduction in revenue due to degradation in the 12–46% range. Moreover, we find that reducing the cycling of the battery via introducing a penalty cost in the objective function of the energy arbitrage optimization model can improve the profitability over the life of the BESS.